Efficacy and Safety of AEZS-108 (LHRH Agonist Linked to Doxorubicin) in Women With Advanced or Recurrent Endometrial Cancer Expressing LHRH Receptors: A Multicenter Phase 2 Trial (AGO-GYN5). Issue 2 (1st February 2014) - Emons, Günter; Gorchev, Grigor; Harter, Philipp; Wimberger, Pauline; Stähle, Anne; Hanker, Lars; Hilpert, Felix; Beckmann, Matthias W.; Dall, Peter; Gründker, Carsten; Sindermann, Herbert; Sehouli, Jalid
Abstract : Objective: Advanced or recurrent endometrial cancer (EC) no longer amenable to surgery or radiotherapy is a life-threatening disease with limited therapeutic options left. Eighty percent of ECs express receptors for luteinizing hormone–releasing hormone (LHRH), which can be targeted by AEZS-108 (zoptarelin doxorubicin acetate). This phase 2 trial was performed to assess the efficacy and safety of AEZS-108 in this group of patients. Methods: Patients had FIGO (Fédération Internationale de Gynécologie et d'Obstétrique) III or IV or recurrent EC, LHRH receptor–positive tumor status, and at least had 1 measurable lesion (Response Evaluation Criteria in Solid Tumors). Prior anthracycline therapy was not allowed. Patients received AEZS-108 as a 2-hour infusion on day 1 of a 21-day cycle. The treatment was continued for a maximum of 6 to 8 cycles. The primary end point was the response rate determined by the Response Evaluation Criteria in Solid Tumors. Results: From April 2008 to November 2009, 44 patients were included in the study at 8 centers in Germany (AGO) and 3 centers in Bulgaria. Forty-three of these patients were eligible. Two (5%) patients had a complete remission, and 8 (18%) achieved a partial remission. Stable disease for at least 6 weeks was observed in 44%. The median time to progression was 7 months, and the median overall survival was 15 months. The most frequently reported grade 3 or 4 adverse effects were neutropenia (12%) and leucopenia (9%). Conclusions: AEZS-108, an LHRH-agonist coupled to doxorubicin, has significant activity and low toxicity in women with advanced or recurrent LHRH receptor–positive EC, supporting the principle of receptor-mediated targeted chemotherapy.